The Effectiveness and Integrity of Online assessments Using Moodle Learning Management System: Perspectives of a Developing country’s university teachers - Owusu-Oware, Emmanuel; Tanye, Hannah Ayaba (The journal of contemporary issues in business and government, 2023)
Learning management systems in higher education contexts attained significance in digital innovations during the COVID-19 pandemic when many universities switched suddenly to online mode of teaching and learning. While many universities continue to use learning management systems to supplement face-to-face teaching and learning, academics are concerned about the efficacy and integrity of the online examination environment. This study uses empirical survey data to investigate the case of a developing country university in Ghana that has been using Moodle learning management system for online assessments since 2019 to supplement in-person assessments. The study examined the university’s teachers’ use of learning management system tools for assessments, their perceptions of the effectiveness/integrity of these tools for examinations, and the challenges involved. This paper presents the results of the study.